Primacy Of Beautiful and Good Speech (Qawlan Hasanan) in Islamic Communication Ethics - Malik, Mohammad Manzoor (Arts of Management Journal, 2026)
Although Islamic communication ethics has received growing scholarly attention, relatively little work has examined Qawlan Hasanan as a comprehensive normative framework grounded in the Quranic concept of human dignity (karamah) and applicable to both interpersonal and digital communication. This article addresses that gap by examining the Quranic concept of Qawlan Hasanan (beautiful and good speech) as the foundational principle of Islamic communication ethics. The study employs qualitative textual and thematic analysis of relevant Quranic verses and Prophetic traditions (Hadith) to reconstruct the conceptual structure of Qawlan Hasanan within the broader framework of Islamic moral theology and communication ethics. The analysis systematically relates Qawlan Hasanan to other Quranic categories of ethical speech and explores its implications for interpersonal and digital communication. The study finds that Qawlan Hasanan functions as an overarching ethical category integrating truthful, gentle, respectful, honorable, and socially constructive speech into a unified communicative framework. Rather than merely prescribing polite language, it grounds communication in the intrinsic dignity (karamah) of every human being, linking moral speech with faith, moral accountability, social trust, peaceful coexistence, and responsible digital citizenship. The framework simultaneously condemns verbal abuse, ridicule, misinformation, and hate speech as violations of human dignity and social harmony. Theoretically, the article advances Islamic communication ethics by conceptualizing Qawlan Hasanan as a comprehensive dignity-centered model of ethical communication applicable to both offline and online contexts. In doing so, the paper reframes Qawlan Hasanan not as etiquette but as a dignity-grounded communicative ethics.